The subgingival cultivable bacteria of Albanian subjects with different periodontal status compared to a similar population of Spanish subjects: a case control study - Gerila Tafaj; Margarita Iniesta; Mariano Sanz; David Herrera (BMC, 2022)
Abstract Background The objective was to qualitatively and quantitatively describe the subgingival cultivable bacteria in Albanian subjects and to compare it with a similar Spanish population. Materials and methods Consecutive patients, diagnosed as periodontitis in stages I-II or III-IV, and as periodontally healthy or with gingivitis, were studied clinically and microbiologically by means of microbiological culture, including total anaerobic counts, proportions, and frequency of detection of target species. Outcome variables were analysed by Mann-Whitney, Kruskal-Wallis, ANOVA, ANCOVA and Chi-square tests. Results In this cross-sectional study, 83 (Albania) and 90 (Spain) subjects were included. No statistically significant differences were observed between test and control populations regarding demographic variables or smoking habit. Significantly higher total anaerobic counts in the Albanian population (p = 0.022) were observed, especially in the periodontal health/gingivitis group (p = 0.001). In the test population, the proportions of the cultivable bacteria of Fusobacterium nucleatum were significantly lower in both the healthy/gingivitis (p = 0.022) and stages I-II periodontitis (p = 0.034) groups. Conclusions The subgingival cultivable bacteria in both periodontitis and non-periodontitis subjects from Albania showed significantly higher total anaerobic counts and lower proportions of the cultivable bacteria of F. nucleatum than a similar population of subjects from Spain.